A performance-based budget in the judiciary: allocation of resources and performance variability in first instance courts. An analysis of three case studies. Issue 2 (12th October 2020) - Viapiana, Federica
Abstract : Purpose: The purpose of this paper is to compare the different performance-based budgeting models used in the judiciaries of three European countries: Italy, Finland and the Netherlands. In particular, this paper focusses on the criteria adopted by these three countries to fund the courts, and it analyses the effects of these criteria on the distribution of resources and performance variability among first instance courts. Design/methodology/approach: This exploratory research is based on a literature review and data analysis of three case studies. Equity in resource distribution and equality in courts' performance are assessed using the coefficient of variation. Findings: The preliminary findings suggest the following: (1) funding models with a close link between performance and budget better guarantee equitable allocation of resources among courts and, therefore, more equal performance among courts within a country; (2) unbalanced allocation of resources is associated with disparities among courts in terms of judicial efficiency and effectiveness and consequently, unequal treatment of/outcomes for citizens coming before the law. Research limitations/implications: This paper is part of a broader research project aimed at analysing the impact of performance budgeting on the efficiency, quality, organization and values of judiciaries. This study only considers quantitative aspects of performance, but it will be followed by further analysis that will explore performance and judicial budgeting from other perspectives. Practical implications: This paper describes examples of three different models of performance-based judicial budgeting from other countries, which aim to reform the budgeting processes of the judiciaries in question. The paper emphasizes the importance of adopting rational and transparent funding criteria in order to ensure judicial independence and accountability and to balance courts' performance, guaranteeing the principle that every citizen must obtain the same treatment before the law. Originality/value: This paper contributes to the existing performance-based budgeting literature by studying its application to the judiciary, which, due to its peculiarities, is an area that has been overlooked in previous studies and deserves further attention. This study contributes to the court administration literature by exploring the issue of budgeting, which, despite its importance, is still a neglected subject.